Destination selection by aging travelers: a literature review - Verma, Vimal Chandra; Kaur, Simran; Meiners, Norbert (REVISTA QUAESTIO IURIS, 2022)
Abstract Purpose: Today, the rapid increase in the population of Golden Agers has rapidly increased the concept of "gray-pride". According to World Age Structure (2018),the population aged 55-64 was estimated at 8.84%, while the population aged 65 years and above was estimated at 9.06%. With their growing interest in adventurous activities, the tourism industry has begun to understand the importance of this ’forgotten’ niche. The unique wants and needs of this group have necessitated understanding the different factors that influence travellers among Golden Agers to select a particular destination. Thus, this paper studies the impact of such different factors on aging travellers. Design/methodology/approach: Since the paper is qualitative in nature, different studies conducted between the time period 2016 and 2020 were reviewed and classified according to the factors considered for the study. Findings: The factors such as age, demographics and geography of the location, and activities likely to be undertaken strongly influence tourists, while factors such as facilities provided by internet and "Homestay" also had an influence. Originality/Value: Today’s Golden Age is active, energetic, and has unique needs and desires, specifically when it comes to travel. Marketers and academics alike have considered this group as a "minor niche". While, given their growing population and inclination to travel, few studies have been conducted to understand different factors and their impact on the Golden Age, a combined study of such factors has hardly been addressed. Keywords:Golden Ager, Destination selection, Ageing travelers, Tourism. Resumo Objetivo: Hoje em dia, o rápidoaumento da população de Golden Agers aumentou rapidamente o conceito de "gray-pride". Segundo a World Age Structure (2018), a população entre 55-64 anos foi estimada em 8,84%, enquanto que a população entre 65 anos e mais foi estimada em 9,06%. Com o seu crescente interesse em atividades aventureiras, a indústria do turismo começou a compreender a importância deste nicho "esquecido". Os desejos e necessidades únicas deste grupo obrigaram a compreender os diferentes fatores que influenciam os viajantes entreos Golden Agers a seleccionar um determinado destino. Assim, o presente documento estuda o impacto de fatores tão diferentes sobre os viajantes envelhecidos. Concepção/metodologia/abordagem: Uma vez que o documento é de natureza qualitativa, diferentes estudos realizados entre o período de tempo 2016 e 2020 foram revistos e classificados de acordo com os fatores considerados para o estudo. Conclusões: Os fatores como a idade, demografia e geografia do local, e atividades susceptíveis de serem empreendidas influenciam fortemente os turistas, enquanto fatores como facilidades fornecidas pela Internet e "Homestay" também tiveram influência. Originalidade/Valor: A Idade de Ouro de hoje é ativa, enérgica, e tem necessidades e desejos únicos, especificamente quando se trata de viajar. Tanto comerciantes como acadêmicos têm considerado este grupo como um "nicho menor". Embora, tendo em conta a sua crescente população e a sua inclinação para viajar, poucos estudos têm sido realizados para compreender diferentes fatores e o seu impacto na Idade de Ouro, um estudo combinado de tais fatores dificilmente tem sido tratado. Palavras-chave:Idade de Ouro, Seleção de destinos, Envelhecimento dos viajantes, Turismo.